Managerial grid in macroeconomic perspective: An empirical study (2008–2017). Issue 3 (3rd July 2019) - Roy, Debasish
Abstract: Blake and Mouton's seminal work on leadership style has attracted researchers and been subjected to both praise and criticism from different frontiers. Blake and Mouton's Managerial Grid (BMMG) is a two-dimensional model where the "concern for production" is plotted along the horizontal axis ( X -axis) and the "concern for people" is plotted along the vertical axis ( Y -axis) for a firm/organization. Clearly, BMMG model was established with reference to a microeconomic perspective in mind. This research paper's objectives are two-fold: First; to formulate a Blake and Mouton's Managerial Grid Index (BMMGI) consisting of two proxy independent variables for "concern for production" and "concern for people, " respectively, in a macroeconomic perspective, and second; to individually compare between the estimated and actual results of Blake and Mouton's Managerial Grid Index Area (BMMGIA), calculate the deviation between the two, if any, for each sample observation by applying extrapolation and classify the countries according to the regression results. In order to serve these purposes, empirical analysis has been performed across 11 European countries for the time period of 10 years (2008–2017).